IMPROVING MATHEMATICAL COMMUNICATION CAPABILITIES BY REALISTIC MATHEMATICS APPROACH - Juliati, Juliati; Firman, Muhammad; Nugraha, Derry ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The background of this study is the lack of mathematical communication skills (MCS) of junior high school students in Cimahi. This study aims to examine the achievement and improvement of MCS of junior high school students in Cimahi by realistic mathematical approaches. This study involved two groups, namely the experimental group and the control group. All groups were given a pretest and posttest. The experimental group obtained mathematics learning with realistic mathematical approaches as treatment and control groups obtained mathematics learning as usual as a treatment. This research method is an experimental research with pretest-posttest control group design, namely the design of the pretest posttest control group that involves two groups and randomly sampled classes. The population in this study were junior high school students in Cimahi, while the sample consisted of two randomly selected classes. Obtained class VIII M (experimental class) and class VIII K control class. The instrument used was a 5-item MCS description test, then the skills scores MCS students' were analyzed with descriptive and inferential statistics using assistance Minitab 17. Based on the results of the study, it was concluded that the achievement and improvement of students' MCS using mathematical realistic approaches were better than students who used ordinary learning.